Epigenetic Regulation in Knee Osteoarthritis - Cai, Zhengyu; Long, Teng; Zhao, Yaochao; Lin, Ruixin; Wang, You (Frontiers in Genetics, 2022)
Osteoarthritis (OA) is a complex disease with both environmental and genetic component. Despite increase report of potential risk loci for OA development, it has become evident that genetics are not the definitive cause of osteoarthritis. Epigenetics, which can be induced by environmental factors and lead to transcriptional changes, can be an important regulatory mechanism in OA pathogenesis. Most current studies on the epigenetics of OA focused on DNA methylation, histone modification and non-coding RNAs. Here, we will have an overview on the current understanding of epigenetic regulation in OA. We will explore the interactions between genetics, environmental factors and epigenetics. and their implications for future research. Their potential mechanisms of interaction and regulation offer new possibilities for the discovery of new therapeutic and diagnostic approaches for osteoarthritis.